2021
DOI: 10.1016/j.amjcard.2020.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Characteristics and Outcomes of Patients With Acute Myocardial Infarction With Versus Without Coronarvirus-19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has greatly impacted the US healthcare system. Cardiac involvement in COVID-19 is common and manifested by troponin and natriuretic peptide elevation and tends to have a worse prognosis. We analyzed patients who presented to the MedStar Health system (11 hospitals in Washington, DC, and Maryland) with either an ST-elevation myocardial infarction (STEMI) or non-ST-elevation myocardial infarction (NSTEMI) early in the pandemic (March 1, 2020 – June 30, 2020) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
27
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 19 publications
7
27
0
2
Order By: Relevance
“…In-hospital death was more frequent in Covid-19 group. This situation was similar in other articles (5).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In-hospital death was more frequent in Covid-19 group. This situation was similar in other articles (5).…”
Section: Resultssupporting
confidence: 91%
“…ndings con rm that Covid-19 is more common at older ages although younger ages are not safe from Covid-19. These ndings are consistent with another study(5), and the age range for MI may be changed if Covid-19 develops in patients.Two models of MI do not have a good prognosis due to poor arteries and multiple stenoses (in NSTEMI) and due to the lack of adequate collaterals (in SVD)(13)(14)(15). LAD was the most involved vessel in the Covid-19 patients with STEMI which may explain the more decrease in EF in them after MI.Injury to the patient's vital organs, including the kidney, is one of the causes of worsening prognosis in patients with ACS.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…One meta-analysis reported that out of hospital cardiac arrests had increased by 120% in five countries (Australia, Italy, Spain, United States, and France) compared to before the pandemic 11 . In-hospital mortality rates for patients presenting with acute coronary syndrome were found to be significantly higher in patients who had COVID-19 (27.9%) compared to those who did not carry the virus (3.7%) as reported by Case et al 12 . Only 20% of patients with acute myocardial infarction and COVID-19 infection underwent coronary angiography in that study 12 .…”
Section: Introductionsupporting
confidence: 50%
“…In-hospital mortality rates for patients presenting with acute coronary syndrome were found to be significantly higher in patients who had COVID-19 (27.9%) compared to those who did not carry the virus (3.7%) as reported by Case et al 12 . Only 20% of patients with acute myocardial infarction and COVID-19 infection underwent coronary angiography in that study 12 . One observational cohort study discovered that during the initial months of the pandemic, deaths from ischemic heart disease and hypertensive disorders significantly increased compared to the months leading up to the pandemic, confirming fears that withholding indicated cardiovascular testing was impacting patient morbidity and mortality 13 .…”
Section: Introductionsupporting
confidence: 50%